PCR-based molecular characterization of Blastocystis hominis subtypes in southwest of Iran - Shahram Khademvatan; Rahim Masjedizadeh; Ehsan Yousefi-Razin; Hamidreza Mahbodfar; Fakher Rahim; Elham Yousefi; Masoud Foroutan (Elsevier, 2018)
Blastocystis hominis is the most common intestinal parasite found in humans and many other hosts. Pathogenicity of Blastocystis sp. remains controversial and it has been suggested that it may be associated with certain subtypes of organism. The aim of this study was to evaluate the molecular epidemiology of B. hominis and its subtype distribution in Ahvaz, southwest of Iran. During 2012-2014, a total of 481 samples were collected from patients referred to the medical laboratory centers in Ahvaz for stool examination. Samples were examined by wet mount, and genomic DNA was extracted from 50 positive samples. PCR was performed using seven primer pairs targeting the SSU rDNA gene and sequenced. 69 (14.35%) samples were found to be positive for B. hominis and the subtypes of 50 samples were identified. Five subtypes (STs) were identified, including: ST1 (22%), ST2 (6%), ST3 (40%), ST4 (2%), and ST5 (8%). 11 (22%) mixed infections were found, of which 5 were a mixture of ST3/ST4. Mixtures of ST1/ST3 and ST1/ST4 were 3, respectively. In this study people infected with ST3 showed the most gastrointestinal symptoms. This is the first study in the population of Ahvaz and indicates the high prevalence of ST3 in this area. The results suggest a possible association between this subtype and pathogenic potential of parasite. Keywords: Blastocystis hominis, Prevalence, PCR, Iran